(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Imaging evaluation of soft tissue tumors is important for the diagnosis, staging, and follow-up. Magnetic resonance imaging (MRI) is the preferred imaging modality due to its multiplanarity and optimal tissue contrast resolution. However, standard morphological sequences are often not sufficient to characterize the exact nature of the lesion, addressing the patient to an invasive bioptic examination for the definitive diagnosis.